PENGARUH SIKAP, BUDAYA KERJA, DAN MOTIVASI KERJA TERHADAP KOMPETENSI GURU TK DI KECAMATAN SUKUN KOTA MALANG - Nurul Siti Fatimah (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2021)
Law No.20 of 2003. Educations is process of changing the attitudes and behavior of a person or group of people in making humans more mature through the process of teaching and learning of activity, school is a collection of organization in which there are various dimensions tha are interrelated with one another. in This research is a researcher conducted using a quantitative approach the method used was correlational and the analisys tool used multiple linear regression with the subjects of kindergarten teachers in Sukun District, Malang City, with a total of 78 kindergarten teachers who have not been certified in 15 clusters of Kindergarten Institutions, Sukun District, Malang City, using probability sampling techniques with proportional random sampling. The results showed that 1)Attitudes have a significant and positive effect on teacher competence; 2)Work culture has a significant and positive effect on teacher competence; 3)Work motivation has an effect on but not significant and positive on teacher competence; 4)Attitudes, work culture and work motivation simultaneously have a significant effect on the competence of kindergarten teachers in Sukun District, Malang City.